OPTIMIZATION OF RUNWAY MAINTENANCE USING THE PAVEMENT CONDITION INDEX METHODS AND APPLIED OF LIFE CYCLE COST ANALYSIS (CASE STUDY : FATMAWATI SOEKARNO AIRPORT) - Amanah, Tody
Maintainance of air transportation especially runway of pavement system in the Fatmawati Soekarno Airport Province of Bengkulu and other airport in Indonesia had high performance, reliable and sustainable. The regulations are suitable that priotize with safety and security. Pavement Condition Index Method are often used for routine inspection activities at major airport in Indonesia, especially inspection for runway of pavement systems. Maintainance management at the runway is also to be able to manage the most optimal maintenance period in terms of economy with the life cycle cost analysis Method. This Thesis examines treatment of costs, treatment of period, and optimization of costs based on a decrease in PCI value due to existing traffic loads at Fatmawati Airport by the several types of treatments scenarioes. It also evaluates the structural performance of the runway pavement system. The results of the primary survey show that the average PCI value in 2018 is 73 (satisfactory). The result of proccecing the secondary data, average PCI value in 2016 is 89 (fair), and in 2017 is 83 (fair). The evaluations results of pavement structural layers obtained the value of PCN > ACN so that it can concluded the structural layer can serve existing flight traffic growth of 10% during the maintenance period of 20 years. Based on the value of PCI for the 3 years and the growth of existing traffic flight, a decrease PCI value can be predicted by the equation models. PCI value prediction in 2019 is 66 (satisfactory), PCI value in 2020 is 60 (satisfactory), and PCI value in 2021 is 54 (poor). Treatment costs are also based on occupation volumes of previous years, unit price analysis, and calculating the present value for 20 years maintainance. Scenarios are based on decreasing the PCI value. The result of the analysis of the scenarios that area can be known that the most minimal treatment costs are fourth scenarios with the type of treatment is scrape and fill each 7 years when the PCI value is reach 60 (satisfactory). The recommendation that can be implemented with UPBU Fatmawati Airport in Province of Bengkulu with the amount of runway pavement maintenance costs for the maintainance periods is Rp 101.713.401.085,- is the fourth scenario.